Data Engineering Approaches (International Journal of Engineering and Computer Science, 2018)
The government of Tegal city doesn’t currently have the media used to publicize land use, the socialization of land use is rarely done, so that this may cause some problems, such as: there is land used for facilities that are not, the efficiency of land use is not maximal, the existing public services in the city of Tegal become obstructed and inhibit the productivity of existing resources in the city of Tegal. Land Use Mapping System in Tegal City Area becomes a solution to the problems. The system is made based on the website that can be used as a media mapping of land use area contained in the city of Tegal. The system can also present comparisons of land use in the Tegal area of ​​the city each year differently, in addition the system can also be updated easily.